(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The performance of the banking sector is one of the key elements in supporting economic growth and increasing national stability. Information published by companies such as company financial reports, financial ratios, banking economic growth can influence investment decisions. This research aims to determine and analyze the influence of dhi banking risk. credit risk (NPL) and liquidity risk (LDR) on stock returns with profitability (ROA) as an intervening variable. The subjects of this research are banking sector companies listed on the Indonesia Stock Exchange in the 2017 - 2021 period with research variables in the form of NPL (X1), LDR (X2), ROA (Z) and Stock Return (Y). The data analysis technique used is the structural equation modeling approach and path analysis with the help of the SPSS AMOS 25 application. The results of this study show that Non-Performing Loans (NPL) have a significant effect on Return on Assets (ROA) but have no effect on Stock Returns; Loan to Deposit Ratio (LDR) has no effect on Return on Assets (ROA) and Stock Returns; Return on Assets (ROA) has no effect on Stock Returns. Return on Assets (ROA) cannot mediate the relationship between Non-Performing Loans (NPL) and Stock Returns and also cannot mediate the relationship between Loan to Deposit Ratio (LDR) and Stock Returns.